(untitled) (International Journal of Artificial Intelligence Engineering and Systems, 2026)
The proliferation of latency-sensitive, bandwidth-intensive, and ultra-reliable applications across fifth-generation mobile networks has fundamentally transformed the requirements placed upon traffic engineering in the core network. The 5G core, built on service-based architectures and network slicing, demands dynamic, fine-grained, and quality-of-service-aware routing decisions that operate at unprecedented scale and complexity. Traditional optimization heuristics and early machine learning approaches have struggled to maintain both performance and adaptability under such conditions. This paper presents a novel collaborative architecture that integrates deep reinforcement learning with large language models to achieve continuous, context-aware traffic engineering governed by explicit quality-of-service objectives. In this design, a deep reinforcement learning agent learns forwarding policies through interaction with a high-fidelity simulation of the core network, while a large language model functions as a semantic reasoning module, interpreting natural language operator intent, generating policy templates, and providing high-level guidance to constrain the reinforcement learning action space. The architecture is examined from system-level perspectives including modular composition, training stability, inference latency trade-offs, and the division of labor between learned control and symbolic reasoning. Particular attention is devoted to the implications of such a dual-model system for infrastructure sustainability, governance, fairness, and robustness in multi-tenant network environments. The paper further analyzes how collaborative intelligence architectures can absorb emerging traffic prediction models, referencing recent advances in spatial-temporal intelligence, and addresses deployment pathways that align with the ongoing softwarization of telecom infrastructure. Critical policy dimensions such as algorithmic transparency, slice isolation guarantees, and resource allocation equity are discussed as intrinsic design requirements rather than afterthoughts. The analysis suggests that hybrid architectures combining subsymbolic learning with the compositional reasoning capabilities of large language models represent a viable trajectory for the next generation of autonomous network management systems.